Wudhu As a Succession of Mental Revolution For Future Generation - Dian Cita Sari (Journal of Educational Science and Technology (EST), 2018)
Ablution contains many values that can be used as supporting the education of future generations of Muslim characters. The mental revolution is a rapidly changing way of thinking to change the order of Indonesian society to be a leader in a trustful and honest future to bring the nation of Indonesia into a better and prosperous future. The mental revolution is aimed at ensuring that Indonesians can become a politically sovereign, economically self-sufficient and socially-socio-cultural country so that they can realize an independent, just, prosperous, civilized and civilized society. Mental revolution can utilize ablution as a process of education of character / mental revolution of future generation Indonesia to bring the nation of Indonesia go to the happiness of life in the world and the hereafter. Through wudu, educators can make multi-use values, both physical health and psychic health as a succession of character education / mental revolution of future generations of Muslims. The location of this research at the Faculty of Medicine and Health, Abdurrab University, Riau. Type of research used is qualitative research because the data will be presented in descriptive analysis.